DIASPORA KHAZANAH BUDAYA KEAGAMAAN MASYARAKAT BALI DI LAMPUNG SELATAN - Yunani, Ahmad; Pinem, Masmedia; Burhanudin, Dede; Nugraha, Mulyawan Safwandy; Salsabila, Nadira (Jurnal Lektur Keagamaan, 2023)
ABSTRACT The purpose of this study is to explore the various diaspora forms of the Balinese ethnic community's religious and cultural traditions, specificially in Tridharmayoga Village in South Lampung. The island of Bali is recognized for its unique Hindu religious traditions which mirror the indigenous culture. It is observed that when the Hindu Balinese community migrates to transmigration areas or other regions exterior to Bali, they persist in practicing these traditions as a component of their Hindu identity. The Tridharmayoga Village was founded on the principles of three diaspora religions: Hinduism, Islam and Catholicism. The village promotes interacttions that place a high emphasis on unity, despite the changes in religious traditions and cultural practices that might diverge from the native homeland. However, these traditions remain prevalent in the diaspora region. Considering these factors, questions emerge regarding the Balinese diaspora's presence in this village and how the Balinese ethnic group's religious and cultural heritage traditions, inherited from their homeland, are expressed in this new environment. This research adopts an exploratory and qualitative descriptive-analytical approach, presenting data descriptively based on the empirical evidence collected from the field. Data were collected through observations, interviews, and document analysis from a variety of sources in the field. The findings of this study indicate that the village, which is rooted in unity, diversity, and multiculturalism, adjusts its religious traditions to align with the established culture. This adjustment, however, does not eradicate the fundamental traditions but modifies them to suit the economic conditions of the host land, ensuring adherence to obligatory practices. This study offers insights into the value transformation within the religious traditions of the Balinese ethnic group, influenced by specific local conditions, particularly focusing on the Hindu Balinese community in Tridharmayoga Village. Keywords: Diaspora, Religious Culture, Balinese Hindu Ethnicity, Tridharmayoga Village, South Lampung.   ABSTRAK Tulisan ini bertujuan untuk mengidentifikasi dan menganalisis bentuk diaspora tradisi khazanah budaya keagamaan dari komunitas diaspora etnis Bali, khususnya di Desa Tridharmayoga Lampung Selatan. Sebagaimana diketahui bahwa di Bali tradisi keagamaan Hindu memiliki ciri khas tersendiri yang mencerminkan budaya lokal. Ketika masyarakat Hindu Bali pindah ke daerah transmigrasi atau wilayah lain di luar Bali, mereka akan tetap menjalankan tradisi tersebut sebagai Hindunya. Desa Tridharmayoga dibangun atas dasar tiga agama diaspora; yaitu Hindu, Islam dan Katolik. Interaksi yang dibangun di desa ini sangat menjunjung tinggi kebersamaan, meskipun ada pergeseran tata tradisi dan budaya keagamaan yang agak berbeda dengan tradisi daerah asal. Akan tetapi masih menjadi tradisi yang dominan daerah perantauan. Karenanya berdasarkan hal tersebut, maka muncul permasalahan tentang bagaimana keberadaan orang Bali di Desa ini, dan bagaimana tradisi Khazanah Budaya Keagamaan etnis Bali yang sudah mentradisi di negeri asal mereka?. Penelitian bersifat eksploratif, dan merupakan penelitian deskriptif analitis kualitatif, yakni menyajikan data secara deskriptif sesuai data dan fakta yang ditemukan di lapangan. Data dikumpulkan dari berbagai sumber di lapangan melalui observasi atau pengamatan, wawacara, dan studi dokumen. Temuan yang didapat adalah bahwa desa ini yang dibangun atas dasar kebersamaan dan keragaman serta multikultur, karenanya tradisi keberagamaan yang dilaksanakan menyesuaikan dengan kultur yang telah dibangun, akan tetapi tidak menghilangkan tradisi yang semestinya dilakukan, hanya saja sehubungan dengan keberadaannya berada di tanah rantau, maka dalam pelaksanaannya disesuaikan dengan kondisi perekonomian yang ada tanpa menghilngkan kewajiban kewajiban yang harus dilakukan.. Penelitian ini diharapkan mendapatkan gambaran terjadinya transformasi nilai dalam tradisi keagamaan etnis Bali yang disebabkan dengan kondisi lokal tertentu, khususnya etnis Hindu Bali di Desa Tridharmayoga.   Kata Kunci: Diaspora, Budaya Keagamaan, Etnis Hindu Bali, Desa Tridharma Yoga, Lampung Selatan